Retificação de aço endurecido com aplicação de fluido de corte pela técnica MQL contendo grafeno e nanotubos de carbono - Abrão, Bruno Souza (2022)
The abrasion machining process has wide application in several industrial sectors for achieving the combination of low roughness values (Ra < 1.6 µm) and narrow dimensional tolerances (IT6 to IT3), however it is a process in which a high specific energy is generated. The abrasive material of conventional grinding wheels has low thermal conductivity and the chips generated are small, so that most of the heat is directed to the workpiece, so becoming essential to use cutting fluid to cool the cutting area. The cooling system most used for grinding is the conventional technique of supplying cutting fluid (flooding). However, due to the growing concern with work safety, environmental and economic issues, it became necessary to study new ways of applying the cutting fluid, with emphasis on the Minimum Quantity of Lubrication (MQL). On the other hand, the MQL technique has limitations regarding the process temperature reduction, which has motivated the development of a new line of research, among them the one that adds solid particles to the fluid to improve the cooling and lubrication functions. In this sense, the present work aimed to study the dispersion of carbon nanotubes and graphene particles in the cutting fluid during the external cylindrical plunge grinding of SAE 52100 hardened steel using different types of abrasive grinding wheel (conventional Al2O3 and seeded gel). The following cutting parameters tested were: the feed speed Vf (1.0 mm/min and 1.5 mm/min) and the workpiece speed Vw (0.29m/s and 0.57 m/s). As a result, there was an increase in the roughness and deterioration of the surface texture with the increase in the feed speed and the reduction in the workpiece speed. The use of the seeded gel grinding wheel and the fluid containing the solid particles resulted in a better finish. The highest Vf and lowest Vw generated the highest microhardness variations and increased cylindricity deviations. The use of the seeded gel grinding wheel and the conditions MQL+Graphene and MQL+Carbon nanotubes minimized the occurrence of thermal damage. The grinding power was reduced with the use of the seeded gel grinding wheel and the fluids containing solid particles.